A survey of anticyclonic mesoscale eddies, within the Southern Ocean, and their propagation south from the South West Indian Ridge - Reid, Kirrin Gail (Department of Oceanography, 2017)
Eddies within oceans act as vehicles, transporting smaller bodies of water, with certain oceanographic characteristics, from one place to another within a larger body of water. The South West Indian Ridge [SWIR] is a topographically complex bathymetric feature which amplifies the production of mesoscale eddies in and around the Antarctic Circumpolar Current [ACC]. Within the Southern Ocean [SO], a section of this ridge - the Andrew Bain Fracture Zone [ABFZ] - has been found to be the starting line of an eastward extending eddy corridor. Earlier research shows an area of diminishing mesoscale variability within this corridor which extends down from 45°S to approximately 60S. A recent study focused on a southward extending anticyclonic eddy corridor and proved its existence. The anticyclonic [warm core] eddies which are propagating south, not previously investigated through in situ means, were observed during the 2014 Marion Island Relief Cruise [MIRC2014] aboard the SA Agulhas II. Two anticyclonic mesoscale eddies [one juvenile and one mature] were bisected with transects of conductivity, temperature and depth stations and expendable bathythermograph deployments. This paper used the in situ data captured during the MIRC2014 to study the internal structure of the two eddies. The objectives of this study were also to examine both the recent and the historical trajectory characteristics of the southward advecting anticyclonic eddies, to confirm the origin of the two sampled eddies, and to assess the structural differences between the two anticyclonic eddies. This paper plots the behaviour of the anticyclonic mesoscale eddies found within the area of the southward eddy corridor, firstly using website available data collected over a two year period [May 2012 - May 2014] and then utilizing a previously compiled data set to plot the historical dynamics [October 1992 - April 2012]. The trajectories of the southward anticyclones during that time period were found to be predominantly southward, typically following the south west slope of the SWIR. The two MIRC2014 eddies were confirmed to originate from the ABFZ section of the SWIR. Each eddy had a similar grouping of water masses; Antarctic Bottom Water, Circumpolar Deep Water, Antarctic Intermediate Water, Winter Water and Sub-Antarctic Surface Water: water masses characteristic of the Antarctic Polar Frontal Zone [APFZ]. The in situ measurement and analysis of these eddies allowed the first comparison between a juvenile and a mature anticyclonic eddy in the recently discovered southward extending eddy corridor. Thermal section comparisons of these two sampled anticyclonic eddies showed that, over time, these anticyclonic eddies appear to shrink in surface diameter, deepen and lose heat to host waters. This loss of heat occurs due to the degradation of water mass boundary integrity over time and is theorised to accelerate as time passes. This study shows that the southward extending eddy corridor is a means of shifting heat and salt further south within the SO, large sections of which are sink areas for atmospheric CO₂. This poleward heat transport influences the capability of the SO to absorb atmospheric CO₂, since higher temperatures negatively affect the ocean's CO₂ uptake capability. The results of this study are proposed to be a catalyst for future in situ sampling across eddies in this area, in order that heat and salt transport, through this southward anticyclonic eddy corridor, can be monitored for fluctuations. As this carbon sink is vitally important with regards to climate change, the quantification of the heat and salt sources of the SO, which alter the SO's ability to absorb CO₂, is imperative.